2015
DOI: 10.7860/jcdr/2015/14404.6520
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Release of Nickel and Chromium by Indian Made Orthodontic Appliance in Saliva

Abstract: Average daily release of nickel and chromium over a period of one month was 97.368 μg/day and 47.664 μg/day respectively. The estimated release rates were approximately 32% and 16% of the reported average daily dietary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Based on the the study findings, the amount of chromium ion released after immersion in artificial saliva and the probiotic beverage Lactobacillus casei Shirota strain is still far below the average daily intake of chromium. 14,27,28 This research is in line with previous studies, which concluded that orthodontic appliances are potentially corrosive. Fluctuations in pH and temperature, enzyme and microbial activity, as well as various chemicals that enter the oral cavity are conductors of corrosion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on the the study findings, the amount of chromium ion released after immersion in artificial saliva and the probiotic beverage Lactobacillus casei Shirota strain is still far below the average daily intake of chromium. 14,27,28 This research is in line with previous studies, which concluded that orthodontic appliances are potentially corrosive. Fluctuations in pH and temperature, enzyme and microbial activity, as well as various chemicals that enter the oral cavity are conductors of corrosion.…”
Section: Discussionsupporting
confidence: 92%
“…One of the allergic reactions can be caused by chromium ions. 13,14 An acidic environment is one of the causes of corrosion, which can cause ion release. This is influenced by various factors, including the consumption of beverages that have an acidic pH.…”
Section: Introductionmentioning
confidence: 99%
“…Nilai pelepasan ion nikel pada kelompok minuman probiotik Lactobacillus casei Shirota strain sebanyak 9,69 ppm, sehingga rata-rata hariannya adalah 8,85 μg/L. Jumlah ion yang terlepas tetap harus diperhatikan sesuai dengan jumlah yang dapat ditoleransi oleh tubuh 29,30,31 .…”
Section: Andalas Dental Journalunclassified
“…[5] Various metals that are components of orthodontic alloys have been identified to be allergenic, cytotoxic and mutagenic to oral tissue at different concentration. [26] Elevated levels of zinc in saliva can result in cell cytotoxicity causing oxidative stress and inflammation to epithelial cells. Studies showed ZnO nanoparticles on ingestion or inhalation caused damage to lungs, liver, kidneys and spleen tissue.…”
Section: Introductionmentioning
confidence: 99%